Adapting the nominal group technique for priority setting of evidence-practice gaps in implementation science. Issue 1 (December 2016) - Rankin, Nicole; McGregor, Deborah; Butow, Phyllis; White, Kate; Phillips, Jane; Young, Jane; Pearson, Sallie; York, Sarah; Shaw, Tim
Abstract Background There are a variety of methods for priority setting in health research but few studies have addressed how to prioritise the gaps that exist between research evidence and clinical practice. This study aimed to build a suite of robust, evidence based techniques and tools for use in implementation science projects. We applied the priority setting methodology in lung cancer care as an example. Methods We reviewed existing techniques and tools for priority setting in health research and the criteria used to prioritise items. An expert interdisciplinary consensus group comprised of health service, cancer and nursing researchers iteratively reviewed and adapted the techniques and tools. We tested these on evidence-practice gaps identified for lung cancer. The tools were pilot tested and finalised. A brief process evaluation was conducted. Results We based our priority setting on the Nominal Group Technique (NGT). The adapted tools included a matrix for individuals to privately rate priority gaps; the same matrix was used for group discussion and reaching consensus. An investment exercise was used to validate allocation of priorities across the gaps. We describe the NGT process, criteria and tool adaptations and process evaluation results. Conclusions The modified NGT process, criteria and tools contribute to building a suite of methods that can be applied in prioritising evidence-practice gaps. These methods could be adapted for other health settings within the broader context of implementation science projects.